Frequency of Interim Reporting and Impairment Losses on Financial Assets - Ana Clara Ferreira; Ana Morais (BBR: Brazilian Business Review)
This study investigates the impact that increasing the frequency of interim reporting has on the amount of impairment losses on financial assets for a sample of listed banks. The difference-in-differences method is applied for a paired sample of 36 banks of EU-15, between 2009 and 2018. The results suggest the existence of a negative and significant association between the increase in the frequency of interim reporting and the amount of impairment losses on financial assets recognised in the profit or loss. This study is useful for regulators and supervisors, since its conclusions are relevant for the definition of the frequency of interim reporting, showing the consequences of its increase.